Composite coating for surface of ceramic sealing material and preparation method of composite coating
By forming diamond transition layer and diamond-like coating on the surface of the ceramic sealing material matrix, the serious wear problem of ceramic seals in extreme environments is solved, and higher service life and friction and wear performance are achieved.
Patent Information
- Application Number
- CN202411581222.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-03-14
AI Technical Summary
The existing ceramic seals have severe surface wear in extreme environments such as long-term high pressure, high speed, high impact, and strong vibration, making them difficult to meet the needs of long-lived and stable operation.
The diamond transition layer and diamond-like coating are formed on the surface of the ceramic sealing material matrix, and are prepared by hot wire plasma chemical vapor deposition technology and linear ion beam chemical vapor deposition technology to achieve a gradient transition in the mechanical properties between the ceramic sealing material matrix and diamond-like coating.
The mismatch between the diamond-like coating and the matrix interface of the ceramic sealing material is reduced, the service life of the coating is improved, the friction and wear performance of the ceramic seal is significantly improved, and the seal failure situation is reduced.
Smart Images

Figure CN119615105A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sealing materials, and in particular relates to a composite coating used on the surface of a ceramic sealing material and a preparation method thereof. Background Art
[0002] Mechanical seals can effectively prevent leakage of media and are an indispensable sealing method in the chemical, petroleum, metallurgical and other industries. Sealing materials occupy an important position in mechanical seals and largely determine the service capacity of mechanical seals. Due to their excellent mechanical properties, high temperature and high pressure stability and corrosion resistance, ceramic sealing components are widely used in high-parameter mechanical seal fields such as petrochemicals, aerospace and deep-sea drilling. However, as the service environment of mechanical seal pumps becomes increasingly harsh, existing ceramic seals suffer from severe surface wear under extreme environments such as long-term high pressure, high speed, high impact and strong vibration, making it difficult to meet the requirements of long-life stable operation.
[0003] Existing studies have shown that the preparation of wear-resistant and corrosion-resistant diamond coatings on the surface of ceramic sealing materials by chemical vapor deposition (CVD) can improve friction and wear performance while ensuring the good properties of the substrate, and has been used to modify ceramic seals such as silicon carbide / silicon nitride. However, due to the crystal growth characteristics of the diamond coating, the surface of the deposited diamond coating is relatively rough, resulting in a high initial friction coefficient, and will increase the possibility of mechanical seal failure and leakage during the friction running-in stage. At present, diamond-coated seals need to be polished for a long time before use or use a micron-composite ultra-nano diamond structure coating, and the process is relatively cumbersome or has poor repeatability. Summary of the invention
[0004] In order to solve the above-mentioned technical problems, the present invention provides a composite coating for the surface of a ceramic sealing material and a preparation method thereof to overcome the shortcomings of the prior art. The present invention comprises a diamond coating transition layer on the surface of a ceramic sealing material substrate and a diamond-like coating on the top layer. The diamond coating in the composite coating adopts hot wire plasma chemical vapor deposition technology as a transition layer, which realizes a gradient transition of mechanical properties between the ceramic sealing material substrate and the diamond-like coating, reduces the mismatch between the interface of the diamond-like coating and the ceramic sealing material substrate under reciprocating friction conditions, and improves the service life of the coating.
[0005] The present invention provides a composite coating for the surface of a ceramic sealing material, comprising a diamond transition layer located on a ceramic sealing material substrate and a diamond-like coating located on the diamond transition layer, wherein the diamond transition layer has a thickness of 3-20 μm, a surface hardness of 50-100 GPa, and a grain size of 10 nm to 5 μm, and the diamond-like coating comprises a diamond phase and a graphite phase, wherein the diamond-like coating has a thickness of 0.2 to 10 μm, and a surface hardness of 20 to 30 GPa.
[0006] Compared with the prior art, the present invention has the following advantages: the diamond-like carbon coating (DLC) is mainly composed of C-sp 3 Bond and graphite phase C-sp 2 It is a mixture of diamond and carbon bonds, and has excellent properties such as high hardness, wear resistance, lubrication, and strong chemical inertness. At the same time, as an amorphous material, it has the function of smoothing the surface during the vapor deposition growth process. The DLC modification treatment of existing diamond coated seals can not only smooth the surface of the diamond coated seals, but also play the role of DLC coating in reducing friction and lubrication, significantly shorten the friction running-in stage, reduce the friction coefficient and wear rate of the diamond coating, and improve the life and performance of ceramic seals. The coating includes a diamond coating transition layer and a diamond-like top layer deposited on the surface of the substrate in sequence. The diamond coating forms a gradient transition of the component structure between the diamond-like coating and the ceramic sealing material substrate to achieve high load-bearing capacity of the composite coating. The surface DLC smoothes the surface of the diamond coating and reduces wear, which greatly improves the friction and wear performance of the ceramic seals, increases the service life of the components, and reduces the failure of the seal under actual working conditions.
[0007] In some embodiments, the tribological properties of the composite coating and the silicon carbide ball pair in a 3.5wt% NaCl solution are tested using a ball-on-disc friction and wear tester: the friction coefficient is 0.07-0.1, and the wear rate of the composite coating is 5×10 -6 ~2×10 -5 mm 3 / (Nm).
[0008] The second object of the present invention is to provide a method for preparing a composite coating, the preparation method specifically comprising the following steps:
[0009] S1. Depositing a diamond coating on the surface of a ceramic sealing material substrate by a hot wire plasma chemical vapor deposition method;
[0010] S2. Using a linear ion beam chemical vapor deposition method, a diamond-like coating is deposited on the surface of the diamond coating obtained in step S1 to obtain a composite coating on the surface of the ceramic sealing material.
[0011] In some embodiments, in step S1, the material of the ceramic sealing material matrix is selected from one of silicon carbide, silicon nitride, aluminum oxide, zirconium oxide, and tungsten carbide.
[0012] In some embodiments, in step S1, the parameters of the hot filament plasma chemical vapor deposition method are as follows: methane, hydrogen and nitrogen with a flow ratio of 1-100:0-5:100-10 are used as working gases, the pressure is 1-5kPa, the temperature is 600-1000°C, the distance between the tantalum wire and the ceramic sealing material substrate is 5-20mm, and the deposition time is 5-24h.
[0013] In some embodiments, in step S2, the parameters of the linear ion beam chemical vapor deposition method are as follows: acetylene or methane is used as the working gas, a bias voltage of -50 to -350 V is applied to the surface of the diamond coating, an ion source current of 0.1-0.8 A, and a chamber pressure of 2×10 -5 -5×10 -5 Torr, the flow rate of working gas is 30-40sccm, and the deposition time is 15-750min.
[0014] In some embodiments, in step S1, before depositing the diamond coating, the process of pretreating the ceramic sealing material substrate is also included, and the pretreatment includes grinding treatment. The specific steps are as follows: using an aqueous solution containing 5-15% diamond micropowder with a particle size of 10-100 μm, the ceramic sealing material substrate is ground on a grinder for 5-20 minutes.
[0015] In some embodiments, in step S2, before depositing the diamond-like coating, the step further includes etching the diamond transition layer obtained in step S1, wherein the etching process specifically includes the following steps: using linear ion beam chemical vapor deposition technology, using argon as the working gas, applying a bias voltage of -50 to -350 V on the diamond transition layer, an ion source current of 0.1 to 0.8 A, and a chamber pressure of 2×10 -5 ~5×10 -5 Torr, the flow rate of working gas is 30-40sccm, and the time is 20-50min.
[0016] Compared with the prior art, the present invention uses ceramic sealing material as the substrate, firstly deposits a diamond coating with a thickness of 3 to 20 μm on the substrate surface as an intermediate layer to play a role in the gradient transition and support of the interface between the substrate and the top layer, and then deposits a surface amorphous carbon coating to smooth the surface of the diamond coating and reduce wear, thereby forming a diamond / amorphous carbon composite coating. The excellent performance of the composite coating is as follows:
[0017] (1) The diamond intermediate layer improves the support capacity of the top amorphous carbon coating while reducing the impact of the interface mismatch between the ceramic sealing material substrate and the amorphous carbon coating, reducing the overall internal stress of the composite coating, which is beneficial to improving the film-substrate bonding strength;
[0018] (2) The surface DLC deposition process is simple and stable, which solves the problem that the existing diamond coating polishing process is relatively complicated or has poor repeatability. In addition, the diamond coating is prepared by hot wire plasma chemical vapor deposition technology, and the DLC coating is prepared by linear ion beam chemical vapor deposition technology, which is easy to realize the industrial preparation of the coating;
[0019] (3) In a 3.5wt.% NaCl solution environment, the friction running-in stage of the composite coating is the shortest, the friction coefficient is stable at 0.07-0.1, and the wear rate is lower than that of the diamond coating, showing excellent friction and wear properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The friction coefficient curves of the composite coatings prepared in Example 1 and Example 2 of the present invention, the diamond coating prepared in Comparative Example 1, and the amorphous carbon coating prepared in Comparative Example 2;
[0021] Figure 2 This is a comparison chart of the wear rates of the composite coatings prepared in Example 1 and Example 2 of the present invention, the diamond coating prepared in Comparative Example 1, and the amorphous carbon coating prepared in Comparative Example 2;
[0022] Figure 3 The morphology of the ink marks observed under a light microscope after the composite coating prepared in Example 1 of the present invention was rubbed for 1 hour;
[0023] Figure 4 The figure is the ink mark morphology observed under a light microscope after the diamond coating prepared in Comparative Example 1 of the present invention was rubbed for 1 hour. DETAILED DESCRIPTION
[0024] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.
[0025] It should be noted that the endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.
[0026] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer.
[0027] The technical effects of the present invention are described below in conjunction with specific embodiments.
[0028] Embodiment 1:
[0029] This embodiment provides a composite coating on the surface of silicon carbide, which is composed of a diamond intermediate layer and a vapor-deposited amorphous carbon coating. The bottom layer uses hot wire plasma chemical vapor deposition technology to form a diamond intermediate layer on the surface of the silicon carbide substrate, and the top layer uses chemical vapor deposition technology to prepare a DLC coating; the thickness of the diamond intermediate layer is about 10μm, and the thickness of the amorphous carbon coating is about 2.4μm.
[0030] The preparation method of the composite coating comprises the following steps:
[0031] Step 1: Grind the surface of the silicon carbide substrate using an aqueous solution containing 10% diamond powder with a particle size of 50 μm, and grind it on a grinder for 20 minutes.
[0032] Step 2: The ground silicon carbide substrate is placed in ethanol containing 5% 300nm diamond powder, ultrasonically cleaned for 30 minutes, and then taken out and dried.
[0033] Step 3: Using hot wire plasma chemical vapor deposition technology, with methane / hydrogen / nitrogen as the working gas, the ratio is 3:100:5, the pressure is 3 kPa, the temperature is 800°C, the distance between the tantalum wire and the substrate is 10 mm, the deposition time is 12 hours, and a 10 μm diamond coating is formed on the surface of the substrate with a grain size of 2 μm.
[0034] Step 4: Linear ion beam chemical vapor deposition technology was used, with argon as the working gas, a bias voltage of -200 V was applied to the silicon carbide substrate, the ion source current was 0.2 A, and the chamber pressure was 3×10 -5 Torr, the gas flow rate is 38 sccm, and the substrate surface is etched using ionized argon ions. This process is maintained for 30 minutes.
[0035] Step 5: Linear ion beam chemical vapor deposition technology was used, acetylene was used as the working gas, a bias voltage of -100 V was applied to the silicon carbide substrate, the ion source current was 0.2 A, and the chamber pressure was 3×10 -5 Torr, the gas flow rate was 38 sccm, the deposition time was 180 min, and an amorphous carbon coating with a thickness of 2.4 μm was deposited on the surface of the diamond coating.
[0036] The test shows that the friction coefficient between the composite coating and the silicon carbide ball is 0.07-0.1. Figure 1The friction coefficient curves of the composite coatings prepared in Example 1 and Example 2 of the present invention, the diamond coating prepared in Comparative Example 1, and the amorphous carbon coating prepared in Comparative Example 2; Figure 2 This is a comparison chart of the wear rates of the composite coatings prepared in Example 1 and Example 2 of the present invention, the diamond coating prepared in Comparative Example 1, and the amorphous carbon coating prepared in Comparative Example 2; Figure 3 The morphology of the ink marks observed under a light microscope after the composite coating prepared in Example 1 of the present invention was rubbed for 1 hour; Figure 1 It can be seen that the average wear rate of the composite coating prepared in this embodiment is 9.18×10 -6 mm 3 / (Nm), by Figure 2 It can be seen that the composite coating prepared in this embodiment is subjected to friction in a 3.5wt.% NaCl solution for 1h under a load of 5N, and a narrow wear mark is obtained. Figure 3 It can be seen that the composite coating prepared in this embodiment shows excellent friction reduction and anti-wear properties.
[0037] Embodiment 2:
[0038] This embodiment provides a composite coating on the surface of silicon nitride, which is composed of a diamond intermediate layer and a vapor-deposited amorphous carbon coating. The bottom layer uses hot wire plasma chemical vapor deposition technology to form a diamond intermediate layer on the surface of the silicon nitride substrate, and the top layer uses chemical vapor deposition technology to prepare a DLC coating. The thickness of the diamond intermediate layer is about 10μm, and the thickness of the amorphous carbon coating is about 2.4μm.
[0039] The preparation method of the composite coating comprises the following steps:
[0040] Step 1: Grind the surface of the silicon nitride substrate using an aqueous solution containing 10% diamond powder with a particle size of 50 μm, and grind it on a grinder for 20 minutes.
[0041] Step 2: The ground silicon nitride substrate is placed in ethanol containing 5% 300nm diamond powder, ultrasonically cleaned for 30 minutes, and then taken out and dried.
[0042] Step 3: Using hot wire plasma chemical vapor deposition technology, with methane / hydrogen / nitrogen as the working gas, the ratio is 3:100:5, the pressure is 3 kPa, the temperature is 800°C, the distance between the tantalum wire and the substrate is 10 mm, the deposition time is 12 hours, and a 10 μm diamond coating is formed on the surface of the substrate with a grain size of 2 μm.
[0043] Step 4: Linear ion beam chemical vapor deposition technology was used, with argon as the working gas, a bias voltage of -200 V was applied to the silicon nitride substrate, the ion source current was 0.2 A, and the chamber pressure was 3×10 -5Torr, the gas flow rate is 38 sccm, and the substrate surface is etched using ionized argon ions. This process is maintained for 30 minutes.
[0044] Step 5: Linear ion beam chemical vapor deposition technology was used, acetylene was used as the working gas, a bias voltage of -100 V was applied to the silicon nitride substrate, the ion source current was 0.2 A, and the chamber pressure was 3×10 -5 Torr, the gas flow rate was 38 sccm, the deposition time was 180 min, and an amorphous carbon coating with a thickness of 2.4 μm was deposited on the surface of the diamond coating.
[0045] The friction coefficient between the composite coating obtained above and the silicon carbide ball is 0.07-0.1. Figure 1 The friction coefficient curves of the composite coatings prepared in Example 1 and Example 2 of the present invention, the diamond coating prepared in Comparative Example 1, and the amorphous carbon coating prepared in Comparative Example 2; Figure 2 The wear rate comparison diagram of the composite coatings prepared in Example 1 and Example 2 of the present invention, the diamond coating prepared in Comparative Example 1 and the amorphous carbon coating prepared in Comparative Example 2; Figure 1 It can be seen that the average wear rate of the composite coating prepared in this embodiment is 1.12×10 -5 mm 3 / (Nm), by Figure 2 It can be seen that the composite coating prepared in this embodiment shows excellent friction reduction and anti-wear properties.
[0046] Embodiment 3:
[0047] This embodiment provides a composite coating on the surface of silicon carbide, which is composed of a diamond intermediate layer and a vapor-deposited amorphous carbon coating. The bottom layer uses hot wire plasma chemical vapor deposition technology to form a diamond intermediate layer on the surface of the silicon carbide substrate, and the top layer uses chemical vapor deposition technology to prepare a DLC coating. The thickness of the diamond intermediate layer is about 3μm, and the thickness of the amorphous carbon coating is about 1μm.
[0048] The preparation method of the composite coating comprises the following steps:
[0049] Step 1: Grind the surface of the silicon carbide substrate using an aqueous solution containing 5% diamond powder with a particle size of 10 μm, and grind it on a grinder for 20 minutes.
[0050] Step 2: The ground silicon carbide substrate is placed in ethanol containing 1% 10 nm diamond powder, ultrasonically cleaned for 30 minutes, and then taken out and dried.
[0051] Step 3: Using hot wire plasma chemical vapor deposition technology, with methane / hydrogen / nitrogen as the working gas, the ratio is 1:100:0, the pressure is 1 kPa, the temperature is 600°C, the distance between the tantalum wire and the substrate is 5 mm, the deposition time is 5 hours, and a 3 μm diamond coating with a grain size of 10 nm is formed on the surface of the substrate.
[0052] Step 4: Linear ion beam chemical vapor deposition technology was used, with argon as the working gas, a bias voltage of -200 V was applied to the silicon carbide substrate, the ion source current was 0.2 A, and the chamber pressure was 3×10 -5 Torr, the gas flow rate is 38 sccm, and the substrate surface is etched using ionized argon ions. This process is maintained for 30 minutes.
[0053] Step 5: Linear ion beam chemical vapor deposition technology was used, acetylene was used as the working gas, a bias voltage of -100 V was applied to the silicon carbide substrate, the ion source current was 0.2 A, and the chamber pressure was 3×10 -5 Torr, the gas flow rate was 38 sccm, the deposition time was 75 min, and an amorphous carbon coating with a thickness of 1 μm was deposited on the surface of the diamond coating.
[0054] Embodiment 4:
[0055] This embodiment provides a composite coating on the surface of silicon carbide, which is composed of a diamond intermediate layer and a vapor-deposited amorphous carbon coating. The bottom layer uses hot wire plasma chemical vapor deposition technology to form a diamond intermediate layer on the surface of the silicon carbide substrate, and the top layer uses chemical vapor deposition technology to prepare a DLC coating. The thickness of the diamond intermediate layer is about 20μm, and the thickness of the amorphous carbon coating is about 8μm.
[0056] The preparation method of the composite coating comprises the following steps:
[0057] Step 1: Grind the surface of the silicon carbide substrate using an aqueous solution containing 15% diamond powder with a particle size of 100 μm, and grind it on a grinder for 20 minutes.
[0058] Step 2: The ground silicon carbide substrate is placed in ethanol containing 10% 500nm diamond powder, ultrasonically cleaned for 30 minutes, and then taken out and dried.
[0059] Step 3: Using hot wire plasma chemical vapor deposition technology, with methane / hydrogen / nitrogen as the working gas, the ratio is 5:100:10, the pressure is 5 kPa, the temperature is 1000°C, the distance between the tantalum wire and the substrate is 10 mm, the deposition time is 24 hours, and a 20 μm diamond coating with a grain size of 5 μm is formed on the surface of the substrate.
[0060] Step 4: Linear ion beam chemical vapor deposition technology was used, with argon as the working gas, a bias voltage of -200 V was applied to the silicon carbide substrate, the ion source current was 0.2 A, and the chamber pressure was 3×10 -5 Torr, the gas flow rate is 38 sccm, and the substrate surface is etched using ionized argon ions. This process is maintained for 30 minutes.
[0061] Step 5: Linear ion beam chemical vapor deposition technology was used, acetylene was used as the working gas, a bias voltage of -100 V was applied to the silicon carbide substrate, the ion source current was 0.2 A, and the chamber pressure was 3×10 -5 Torr, the gas flow rate is 38 sccm, the deposition time is 600 min, and an amorphous carbon coating with a thickness of 8 μm is deposited on the surface of the diamond coating.
[0062] Comparative Example 1:
[0063] This comparative example provides a diamond coating on the surface of silicon carbide, which is a comparative example of Example 1. The preparation steps of the diamond coating are the same as those of Example 1.
[0064] The specific preparation method comprises the following steps:
[0065] Step 1: Grind the surface of the silicon carbide substrate using an aqueous solution containing 10% diamond powder with a particle size of 50 μm, and grind it on a grinder for 20 minutes.
[0066] Step 2: The ground silicon carbide substrate is placed in ethanol containing 5% 300nm diamond powder, ultrasonically cleaned for 30 minutes, and then taken out and dried.
[0067] Step 3: Using hot wire plasma chemical vapor deposition technology, with methane / hydrogen / nitrogen as the working gas, the ratio is 3:100:5, the pressure is 3 kPa, the temperature is 800°C, the distance between the tantalum wire and the substrate is 10 mm, the deposition time is 12 hours, and a 10 μm diamond coating is formed on the surface of the substrate with a grain size of 2 μm.
[0068] After testing, it was found that the initial friction coefficient of the coating obtained above was 0.5 when grinding with silicon carbide balls in 3.5wt.% NaCl solution and under a load of 5N, and the average friction coefficient after rubbing for 1 hour was about 0.3. Figure 1 As shown; the average wear rate is 6.73×10 -5 mm 3 / (Nm), such as Figure 2 As shown in Figure 2, under the same friction conditions, compared with Example 1, the wear rate increased by more than seven times. A 3.5wt.% NaCl solution was rubbed for 1h under a load of 5N to obtain a wider wear scar, as shown in Figure 2. Figure 4 Comparative Example 2:
[0069] This comparative example is a comparative example of Example 2, except that in this comparative example 2, only an amorphous carbon coating is prepared, and the preparation steps of the amorphous carbon coating are the same as those of Example 2.
[0070] The specific preparation method comprises the following steps:
[0071] Step 1: Grind the surface of the silicon nitride substrate using an aqueous solution containing 10% diamond powder with a particle size of 50 μm, and grind it on a grinder for 20 minutes.
[0072] Step 2: The ground silicon nitride substrate is placed in ethanol containing 5% 300nm diamond powder, ultrasonically cleaned for 30 minutes, and then taken out and dried.
[0073] Step 3: Using hot wire plasma chemical vapor deposition technology, with methane / hydrogen / nitrogen as the working gas, the ratio is 3:100:5, the pressure is 3 kPa, the temperature is 800°C, the distance between the tantalum wire and the substrate is 10 mm, the deposition time is 12 hours, and a 10 μm diamond coating is formed on the surface of the substrate with a grain size of 2 μm.
[0074] After testing, it was found that the initial friction coefficient of the coating obtained above was 0.5 when grinding with silicon carbide balls in 3.5wt.% NaCl solution and under a load of 5N, and the average friction coefficient after 1 hour of friction was 0.3. Figure 1 As shown; the average wear rate is 3.01×10 -5 mm 3 / (Nm), such as Figure 2 As shown, under the same friction conditions, the wear rate increases nearly three times compared with Example 2.
[0075] Although the disclosure is disclosed as above, the protection scope of the disclosure is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the disclosure, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. A composite coating for the surface of a ceramic sealing material, characterized in that: The invention comprises a diamond transition layer on a ceramic sealing material substrate and a diamond-like coating on the diamond transition layer, wherein the thickness of the diamond transition layer is 3-20 μm, the surface hardness is 50-100 GPa, and the grain size is 10 nm to 5 μm; the diamond-like coating comprises a diamond phase and a graphite phase, and the thickness of the diamond-like coating is 0.2 to 10 μm, and the surface hardness is 20 to 30 GPa.
2. The composite coating for the surface of ceramic sealing material according to claim 1, characterized in that: The tribological properties of the composite coating and the silicon carbide ball pair in a 3.5wt% NaCl solution were tested using a ball-on-disc friction and wear tester: the friction coefficient was 0.07-0.1, and the wear rate of the composite coating was 5×10 -6 ~2×10 -5 mm 3 / (Nm).
3. A method for preparing a composite coating according to claim 1 or 2, characterized in that: The preparation method specifically comprises the following steps: S1. Depositing a diamond coating on the surface of a ceramic sealing material substrate by a hot wire plasma chemical vapor deposition method; S2. Using a linear ion beam chemical vapor deposition method, a diamond-like coating is deposited on the surface of the diamond coating obtained in step S1 to obtain a composite coating on the surface of the ceramic sealing material.
4. The method for preparing the composite coating according to claim 3, characterized in that: In the step S1, the material of the ceramic sealing material matrix is selected from one of silicon carbide, silicon nitride, aluminum oxide, zirconium oxide, and tungsten carbide.
5. The method for preparing the composite coating according to claim 3, characterized in that: In step S1, the parameters of the hot wire plasma chemical vapor deposition method are as follows: methane, hydrogen and nitrogen with a flow ratio of 1-100:0-5:100-10 are used as working gases, the pressure is 1-5kPa, the temperature is 600-1000°C, the distance between the tantalum wire and the ceramic sealing material substrate is 5-20mm, and the deposition time is 5-24h.
6. The method for preparing the composite coating according to claim 3, characterized in that: In step S2, the parameters of the linear ion beam chemical vapor deposition method are as follows: acetylene or methane is used as the working gas, a bias voltage of -50 to -350 V is applied to the surface of the diamond coating, the ion source current is 0.1-0.8 A, and the chamber pressure is 2×10 -5 -5×10 -5 Torr, the flow rate of working gas is 30-40sccm, and the deposition time is 15-750min.
7. The method for preparing the composite coating according to claim 3, characterized in that: In the step S1, before depositing the diamond coating, it also includes a process of pre-treating the ceramic sealing material substrate, and the pre-treatment includes grinding treatment. The specific steps are as follows: using an aqueous solution containing 5-15% diamond micropowder with a particle size of 10-100 μm, the ceramic sealing material substrate is ground on a grinder for 5-20 minutes.
8. The method for preparing the composite coating according to claim 3, characterized in that: In the step S2, before depositing the diamond-like coating, the step also includes a process of etching the diamond transition layer obtained in the step S1, wherein the etching process specifically includes the following steps: using linear ion beam chemical vapor deposition technology, using argon as the working gas, applying a bias voltage of -50 to -350 V on the diamond transition layer, the ion source current is 0.1 to 0.8 A, and the chamber pressure is 2×10 -5 ~5×10 -5 Torr, the flow rate of working gas is 30-40sccm, and the time is 20-50min.
Citation Information
Cited By
Ceramic surface composite coating for resisting hard particle environment and preparation method thereof
CN120924905A